Examining the Impact of Online Customer Reviews and Live Streaming on Skincare Purchase Decisions Through Purchase Intention - Shofa Qosidatul Ghautsiyyah; Yayuk Sri Rahayu (Journal of Enterprise and Development (JED), 2025)
Purpose: This study investigates the influence of online customer reviews and live streaming on purchasing decisions related to skincare products, with purchase intention serving as a mediating variable. It explores how online reviews and the interactive features of live streaming shape consumer engagement and decision-making processes among Generation Z and Millennial users on social media platforms, particularly TikTok.Method: A quantitative research design was employed using purposive sampling, involving 180 Gen Z and Millennial TikTok users who are active consumers of skincare products. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 software.Results: The findings indicate that online customer reviews exert a significant positive influence on both purchase intention and purchasing decisions. Live streaming significantly affects purchase intention; however, it does not have a direct effect on purchasing decisions. Furthermore, purchase intention is found to mediate the relationship between both online customer reviews and live streaming with purchasing decisions.Practical Implications for Economic Growth and Development: The study provides valuable insights for skincare brands aiming to optimize their marketing strategies on TikTok. By leveraging credible user-generated reviews and engaging live streaming content, businesses can enhance consumers’ purchase intention, thereby potentially increasing sales. These findings contribute to the development of effective social commerce strategies and support the broader growth of the digital economy within local markets.Originality/Value: The novelty of this study lies in its specific focus on TikTok as a social commerce platform and the skincare industry as its market context.